2021
DOI: 10.1002/bit.27858
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of neural stem cells after space flight and simulated microgravity on earth

Abstract: Understanding how stem cells adapt to space flight conditions is fundamental for human space missions and extraterrestrial settlement. We analyzed gene expression in boundary cap neural crest stem cells (BCs), which are attractive for regenerative medicine by their ability to promote proliferation and survival of cocultured and co‐implanted cells. BCs were launched to space (space exposed cells) (SEC), onboard sounding rocket MASER 14 as free‐floating neurospheres or in a bioprinted scaffold. For comparison, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…There are reports indicating that microgravity simulated by ground-based experiments may not have the same cellular effects as space flight conditions. Han et al 44 reported that the genes associated with proliferation and survival were upregulated in mice neural crest stem cells exposed to real space, whereas cells exposed to ground-based sµg upregulated genes associated with differentiation and inflammation. However, other studies indicate similar effects on cells exposed to zero gravity and microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports indicating that microgravity simulated by ground-based experiments may not have the same cellular effects as space flight conditions. Han et al 44 reported that the genes associated with proliferation and survival were upregulated in mice neural crest stem cells exposed to real space, whereas cells exposed to ground-based sµg upregulated genes associated with differentiation and inflammation. However, other studies indicate similar effects on cells exposed to zero gravity and microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…Even if gene expression changes observed in real microgravity are unique, genes found to be differentially expressed in human cells that are incubated in simulated microgravity are, in many cases, altered also in real microgravity. However, this is not valid for all cell types, as observed in human neural crest stem cells cultured in real or simulated microgravity where dysregulated genes belong to markedly different pathways [131]. Generally, cells exposed both to real or simulated space conditions reported less marked gene expression changes in simulated than in space conditions, as for the superoxide dismutase (SOD) gene which resulted in a 4.1-fold upregulation in space microgravity respect to 1.2-fold in a rotating wall vessel (RWV) [99].…”
Section: Non-coding Rnas and Gene Expression Changesmentioning
confidence: 98%
“…Microgravity is not common in daily life, but it has a major impact on astronauts conducting space operations. Microgravity can up- or downregulate differentiation-related genes [ 70 , 71 ], which may lead to a range of related disorders in astronauts, such as bone loss [ 72 ] and cardiovascular disease [ 73 ]. In addition, simulated microgravity conditions may also disrupt the homeostasis of the immune system and lead to dynamic changes in hematopoietic stem cells (HSC) and lineage cells [ 74 ].…”
Section: Mechanical Microenvironment For Stem Cell Growthmentioning
confidence: 99%